2014
DOI: 10.4236/wja.2014.44049
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Virological Failure with Immunological Criteria in First Line ART Patients in a Resource Poor Setting

Abstract: Indroduction: National Aids control Organisation in India implementing National AIDS control program uses WHO's immunological criteria to screen virological failure. Using immunological criteria to detect virological failure has to be assessed. Predicting virological failure with immunological criteria in resource limited settings had low sensitivity. Factors that influence the outcome are studied. Methods: Retrospective study in tertiary care centre for HIV and TB, Chennai, India. Out of 35,044 on ART between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
(12 reference statements)
2
3
2
Order By: Relevance
“…Study participants with HIV RNA level ≥ 1000 copies/mL showed 12.33 times more likely to experience immunological failure (p <0.001) in a median time of 36 months of ART follow up as compared with those who have HIV RNA level less than 1000 copies/mL. Similar results have been reported from India [ 38 ], Nepal [ 33 ], Thailand [ 39 ], London [ 40 ], and USA [ 41 ].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Study participants with HIV RNA level ≥ 1000 copies/mL showed 12.33 times more likely to experience immunological failure (p <0.001) in a median time of 36 months of ART follow up as compared with those who have HIV RNA level less than 1000 copies/mL. Similar results have been reported from India [ 38 ], Nepal [ 33 ], Thailand [ 39 ], London [ 40 ], and USA [ 41 ].…”
Section: Discussionsupporting
confidence: 74%
“…Virological failure was 4.43 times more likely to happen in individuals aged less than 40 years old (AOR(95% CI) = 4.43(1.57–12.46), p = 0.005). This was supported by several studies conducted in Kenya [ 28 , 47 ], South Africa [ 59 ], Burkina Faso [ 44 ], Swaziland [ 55 ], result of systemic review in Sub Saharan Africa [ 26 ], India [ 38 ], Thailand [ 32 ] and Johns Hopkins-North Carolina University [ 60 ]. The possible explanation for this may be due to difference in maturity or lifestyle stability or may be due to work load and hence may forget to take medication properly.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The result of the current study was higher for virological failure than previously conducted research in Ethiopia (i.e., Jimma, 5.3% 50 and Gondar, 4.1% 51 ) and Burkina Faso at 7.5%. 52 However; our finding was lower than the other studies done in Cameron, 23.2% 53 and Kenya, 24%, 54 Liberia, 47%, 55 Zimbabwe, 30.6%, 56 Tanzania 57.1%, 57 32%, 58 Cameroon, 20.6%, 59 Ghana, 16.7%, 60 Togo, 51.6%, 61 Colombia, 20.9%, 62 India, 69.6% 63 and Peru, 24%. 64 This variance might be attributed due to differences in cutoff values of viral RNA copies per mL of plasma to be considered as virological failure, the difference among study participants, duration of follow-up, study design, and variations on the treatment adherence of HAART.…”
Section: Discussioncontrasting
confidence: 72%
“…(9) predicting virological failure with immunological failure showed 62% had virological failure, which was higher than this study. The sensitivity was higher ranging between 60 to 80% for each criterion, which was higher than the present study with positive predictive value was 20 to 91%.…”
Section: Discussioncontrasting
confidence: 72%